Thermal limiting effects in optical plasmonic waveguides. (April 2017) - Ershov, A.E.; Gerasimov, V.S.; Gavrilyuk, A.P.; Karpov, S.V.; Zakomirnyi, V.I.; Rasskazov, I.L.; Polyutov, S.P.
Abstract: We have studied thermal effects occurring during excitation of optical plasmonic waveguide (OPW) in the form of linear chain of spherical Ag nanoparticles by pulsed laser radiation. It was shown that heating and subsequent melting of the first irradiated particle in a chain can significantly deteriorate the transmission efficiency of OPW that is the crucial and limiting factor and continuous operation of OPW requires cooling devices. This effect is caused by suppression of particle's surface plasmon resonance due to reaching the melting point temperature. We have determined optimal excitation parameters which do not significantly affect the transmission efficiency of OPW. Abstract : Highlights: The thermodynamic model was developed to study thermal effects at nanoscale. Developed model considers temperature-dependent permittivity of the nanoparticles. Thermal effects significantly suppress transmission efficiency of plasmonic chains. Optimal parameters for stable operation of plasmonic chains were defined.